Imaging of Hip Arthroplasties: Normal Findings and Hardware Complications - Deshmukh, Swati; Omar, Imran M. (Seminars in Musculoskeletal Radiology, 2019)
Hip arthroplasty is a common and largely successful surgical procedure, often used for the treatment of advanced osteoarthritis. Imaging plays a key role in routine postoperative imaging surveillance as well as the evaluation of post-arthroplasty pain. Radiographs are the first-line imaging modality and may be followed by computed tomography (CT), ultrasound, and/or magnetic resonance imaging (MRI). Recent advancements in imaging techniques allow for metal artifact reduction on CT and MRI. A variety of complications can arise in the setting of arthroplasty: mechanical loosening, component wear-induced synovitis and osteolysis, adverse local tissue reaction, infection, periprosthetic fracture, implant dislocation and/or component displacement, tendinopathy, and neurovascular injury. This article reviews normal and abnormal imaging findings of hip arthroplasty.
Keywords: arthroplasty; hip; imaging; radiographs; magnetic resonance imaging